Nocturnal melatonin increases glucose uptake via insulin-independent action in the goldfish brain - Watanabe, Kazuki; Nakano, Masaki; Maruyama, Yusuke; Hirayama, Jun; Suzuki, Nobuo; Hattori, Atsuhiko (Frontiers in Endocrinology, 2023)
Melatonin, a neurohormone produced by the pineal gland at night, is known to regulate circadian rhythms. It was recently reported that variants in melatonin receptors are associated with an increased risk of hyperglycemia and type 2 diabetes, suggesting that melatonin may be involved in the regulation of glucose homeostasis. Insulin is a key hormone that functions as a regulator of circulating glucose levels and cellular metabolism after food intake in many tissues, including the brain. However, even during sleep without food, cells remain active by glucose intake, but little is known about the physiological effects of nocturnal melatonin on glucose homeostasis. Even during nocturnal sleep, energy is required for cell survival, and the mechanisms of glucose homeostasis in diurnal rhythms are largely unknown. Therefore, the involvement of melatonin in the diurnal rhythm of glucose metabolism, independent of insulin action after food intake, is presumed. In the present study, goldfish (Carassius auratus) was used as a species which have no insulin-dependent glucose transporter type 4 (GLUT4). We found that plasma melatonin levels were significantly increased and insulin levels were significantly decreased during the night in fasted individuals. Furthermore, glucose uptake in the brain, liver, and muscle was significantly increased at night. After intraperitoneal administration of melatonin, glucose uptake in the brain and liver showed significantly greater increases than uptake in the control group. Administration of melatonin significantly decreased plasma glucose levels in hyperglycemic goldfish, but failed to alter insulin mRNA expression and plasma insulin levels. Using an insulin-free medium, we demonstrated that melatonin treatment increased glucose uptake in a dose-dependent manner in primary cell cultures of goldfish brain and liver cells. The addition of a melatonin receptor antagonist decreased glucose uptake in hepatocytes, but not in brain cells. Moreover, treatment with N1-acetyl-5-methoxykynuramine (AMK), a melatonin metabolite in the brain, directly increased glucose uptake in cultured brain cells. Taken together, these findings suggest that melatonin is a possible circadian regulator of glucose homeostasis, whereas insulin acquired its effect on glucose metabolism after food intake.